2018
DOI: 10.24953/turkjped.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of media on the sleep quality in adolescents

Abstract: This study was conducted to evaluate the influence of media devices on sleep quality in adolescents. Applying a descriptive design, the study was carried out with 9th, 10th and 11th grade students (N=392, 52.0% female, average age 16.04±0.86) who were attending Konya High School between the dates of January 18 and 22, 2016. Changes were seen to occur in the wake-up times of those who had either a television or a computer in their bedrooms (p<0.005, p<0.05, respectively). Overall, it was determined that the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 21 publications
(41 reference statements)
5
24
1
Order By: Relevance
“…Sleep duration (≥7 h in 79.0%) of adolescents in our cohort is consistent with the recommended need for at least 8-10 hours of sleep per night by adolescents (24), while together with usual bedtime (after 23.00 o'clock in 67.3%) and wake up time (6.00-7.00 a.m. in 41.7%) data, sleep patterns in our cohort of adolescents fit in line with previous studies in adolescents (mean age of: 15.2 to 16.4 years) that reported an average bedtime of 23.30-24.00 o'clock, sleep duration of 7.0 to 8.1 hours and wakeup time of 6.75-7.55 o'clock (19,25,26).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Sleep duration (≥7 h in 79.0%) of adolescents in our cohort is consistent with the recommended need for at least 8-10 hours of sleep per night by adolescents (24), while together with usual bedtime (after 23.00 o'clock in 67.3%) and wake up time (6.00-7.00 a.m. in 41.7%) data, sleep patterns in our cohort of adolescents fit in line with previous studies in adolescents (mean age of: 15.2 to 16.4 years) that reported an average bedtime of 23.30-24.00 o'clock, sleep duration of 7.0 to 8.1 hours and wakeup time of 6.75-7.55 o'clock (19,25,26).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings support the high prevalence of altered sleep patterns in adolescents including poor sleep quality rates of 60-80% based on subjective assessment methods including PSQI, and negative self-perception of sleep quality with selfrated poor quality by nearly half of adolescents (2,11,19,22). Hence, increase in awareness of the problem seems crucial given the consistently reported trend of insufficient and deteriorating sleep among adolescents along with somatic and psychological adverse impacts on health (3,4,23).…”
Section: Discussionsupporting
confidence: 82%
“…Our model also revealed a strong in uence of internet use on sleep quality, as reported in some previous studies [7,16]. Internet access has contributed signi cantly to African growth in terms of economic and health promotion, but its excessive use has been associated with unwanted health outcomes, particularly psychological, especially in youth.…”
Section: Discussionsupporting
confidence: 84%
“…Another survey involving 166 participants revealed that dependence on stimulants such as caffeine and nicotine was associated with poor quality of sleep and increased psychological distress [15]. Sleep problems have also been associated with internet use, another potentially addictive behavior, among adolescents and young adults [7,16]. In a study that examined the relationship between internet use and sleep-related problems in 1212 adolescents, using the Young Internet Addiction Scale, it was observed that the adolescents who had higher scores reported more problematic sleep habits and sleep problems [17].…”
Section: Introductionmentioning
confidence: 99%
“…A growing proportion of children were curtailing their sleep duration in response to increasing demands and lifestyle changes, such as prolonged studying hours, and introduction of new electronic technologies. Short sleep duration and poor sleep quality were found consistently associated with the Internet use, mobile phone use and number of devices in the bedroom [47][48][49][50]. Public health efforts that encouraged children to have sufficient sleep may be important in preventing SHS by decreasing studying burden and dependency on electronic devices.…”
Section: Discussionmentioning
confidence: 99%